2021
DOI: 10.2807/1560-7917.es.2021.26.28.2100634
|View full text |Cite|
|
Sign up to set email alerts
|

Real-world data shows increased reactogenicity in adults after heterologous compared to homologous prime-boost COVID-19 vaccination, March−June 2021, England

Abstract: Adults receiving heterologous COVID-19 immunisation with mRNA (Comirnaty) or adenoviral-vector (Vaxzevria) vaccines had higher reactogenicity rates and sought medical attention more often after two doses than homologous schedules. Reactogenicity was higher among ≤ 50 than > 50 year-olds, women and those with prior symptomatic/confirmed COVID-19. Adults receiving heterologous schedules on clinical advice after severe first-dose reactions had lower reactogenicity after dose 2 following Vaxzevria/Comirnaty (93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 8 publications
11
57
0
Order By: Relevance
“…The large-scale US study also revealed that local and systemic reactions were less commonly reported by participants 65 years and older compared with those younger than 65 years, which is consistent with our findings. Regarding gender differences, no detailed information was available in the US study, but a UK study reported that reactogenicity was higher among women, consistent with the findings of our study [13].…”
supporting
confidence: 89%
“…The large-scale US study also revealed that local and systemic reactions were less commonly reported by participants 65 years and older compared with those younger than 65 years, which is consistent with our findings. Regarding gender differences, no detailed information was available in the US study, but a UK study reported that reactogenicity was higher among women, consistent with the findings of our study [13].…”
supporting
confidence: 89%
“…In SOTR the combination of two vaccine strategies that offer complementary stimulation of different immune pathways may more effectively induce long-lasting B cell responses and potent T cell responses [27]. The heterologous vaccine schedules, however, might have some short-term disadvantages inducing greater systemic reactogenicity following the boost dose than their homologous counterparts, as shown by preliminary studies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in light of changing recommendations regarding use of Vaxzevria, several countries are now advising individuals previously primed with this vaccine to receive an alternative vaccine as their second dose, most commonly mRNA vaccines such as the BNT162b2 (BNT) COVID-19 vaccine (Comirnaty, Pfizer-BioNTech), administered in a heterologous prime-boost schedule (https://www.has-sante.fr/jcms/p_3260335/en/covid-19-quelle-strategie-vaccinale-pour-les-moins-de-55-ans-ayant-deja-recu-une-dose-d-astrazeneca, accessed on 9 April 2021). Although heterologous vaccine schedules induced greater systemic reactogenicity following the boost dose than their homologous counterparts [127,128], they may have advantages in form of stronger efficacy against multiple SARS-CoV-2 variants, including the worldwide arising Delta variant https://www.medrxiv.org/content/10.110 1/2021.07.13.21260417v1, accessed on 16 July 2021; https://www.medrxiv.org/content/10 .1101/2021.05.19.21257334v2 [129], accessed on 2 June 2021.…”
Section: How Does Severe Covid-19 Manifest In Children and Young?mentioning
confidence: 99%
“…The recognition of them should immediately lead to updated vaccine designs. Although they may have a stronger reactogenicity [127,128], heterologous vaccinations may be a stronger protection because they act complementary in stimulating the cellular and humoral immune response, and memory functions [129].…”
Section: What Are Strong and Measurable Correlations Between Protection And Disease?mentioning
confidence: 99%